2024
DOI: 10.1111/jofi.13337
|View full text |Cite
|
Sign up to set email alerts
|

Nonstandard Errors

ALBERT J. MENKVELD,
ANNA DREBER,
FELIX HOLZMEISTER
et al.

Abstract: In statistics, samples are drawn from a population in a data‐generating process (DGP). Standard errors measure the uncertainty in estimates of population parameters. In science, evidence is generated to test hypotheses in an evidence‐generating process (EGP). We claim that EGP variation across researchers adds uncertainty—nonstandard errors (NSEs). We study NSEs by letting 164 teams test the same hypotheses on the same data. NSEs turn out to be sizable, but smaller for more reproducible or higher rated researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Many of these projects concluded that different but justifiable analytic decisions led to diverging outcomes, sometimes with statistically significant effects in opposite directions (e.g. [ 18 , 28 , 34 ], but see [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these projects concluded that different but justifiable analytic decisions led to diverging outcomes, sometimes with statistically significant effects in opposite directions (e.g. [ 18 , 28 , 34 ], but see [ 23 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Many-analysts projects are a recent innovation, but they have already been adopted in many different fields, including neuroscience [16,17,[24][25][26], economics [27,28], epidemiology [29], ecology [30,31], political science [18] and psychology [19][20][21][22][23][32][33][34][35]. Many of these projects concluded that different but justifiable analytic decisions led to diverging outcomes, sometimes with statistically significant effects in opposite directions (e.g.…”
Section: Introductionmentioning
confidence: 99%